RELATIONSHIP OF PROTEIN AND CARBOHYDRATE CONSTITUENTS OF QUERCUS SERRATA LEAVES WITH THE LARVAL WEIGHT OF OAK TASAR SILKWORM ANTHERAEA PROYLEI J. - GHOSH, M. K.; SRIVASTAVA, R.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
The multiple correlation and Beta coefficient of fifth instar larval dry weight of Antheraea proylei.J. with total sugar and crude protein constituents of Quercus serrata foliage was studied. Positive and significant impact of total sugar and protein existed on larval weight.